2022
DOI: 10.1371/journal.pone.0264456
|View full text |Cite
|
Sign up to set email alerts
|

Core motifs predict dynamic attractors in combinatorial threshold-linear networks

Abstract: Combinatorial threshold-linear networks (CTLNs) are a special class of inhibition-dominated TLNs defined from directed graphs. Like more general TLNs, they display a wide variety of nonlinear dynamics including multistability, limit cycles, quasiperiodic attractors, and chaos. In prior work, we have developed a detailed mathematical theory relating stable and unstable fixed points of CTLNs to graph-theoretic properties of the underlying network. Here we find that a special type of fixed points, corresponding t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Experimental research has demonstrated several ways in which neuronal connectivity is nonrandom with significant higher-order structure 18,21,28,29,31 . Moreover, small models with simple dynamics have shown the relevance of higher-order motifs in the observed activity [60][61][62] while in silico research has showed that the complexity is largely driven by neuronal morphologies 63,64,20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental research has demonstrated several ways in which neuronal connectivity is nonrandom with significant higher-order structure 18,21,28,29,31 . Moreover, small models with simple dynamics have shown the relevance of higher-order motifs in the observed activity [60][61][62] while in silico research has showed that the complexity is largely driven by neuronal morphologies 63,64,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, counting n-simplices can be done systematically for all dimensions, and the maximum dimension attained (at a given graph density) is an indicator of network complexity. Third, counting n-simplices can be efficiently implemented as opposed to counting the "core motifs" or "robust motifs" of Parmelee et al 61 and Curto et al 62 , for which even listing them concretely above dimension 5/6 remains an open problem. Moreover, whilst counting n-simplices and counting directed cycles on n nodes have the same worst-case complexity, increasing exponentially with the number of nodes 66 ; in practice, counting n-simplices can be computed more efficiently, particularly in large sparse graphs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of the functional and dynamical implications of structural motif must be a major consideration for future work. This prospect, however, may bring with it some considerable advantages: Recent work has shown that attractor dynamics may correlate closely with certain structural motifs [38,39], simultaneously narrowing the search space for structural motifs and broadening our ability to empirically validate results in simulation. These challenges will likely not be surmounted by individual research teams.…”
Section: Discussionmentioning
confidence: 99%